Colorectal Cancer Screening and Access to Healthcare in New York City Taxi Drivers - Costas-Muñiz, Rosario (J Immigr Minor Health, 2020)
BACKGROUND: This study examined differences in colorectal cancer screening across sociodemographic, migration, occupational, and health-related factors in a sample of male taxi drivers. METHODS: Male drivers eligible for colorectal cancer screening (CRCS) (≥ 50 years old) were recruited in 55 community-based health fairs conducted during November 2015 to February 2017 in 16 taxi garages or community locations located in Queens, Brooklyn, Manhattan and Bronx. Participants completed a survey that included sociodemographic, migration, occupational, health-related, and cancer screening practices. For this study 33 questions were analyzed. RESULTS: The sample consisted of 137 male drivers, 27% of them had undergone CRCS. Occupation-related factors, including night shifts and driving high numbers of weekly hours, were associated with lower CRCS rates; having a family history of cancer, health insurance, a regular source of primary care, and a routine check-up in the last year, were associated with higher CRCS rates. DISCUSSION: The findings suggest that drivers with health insurance and better access to primary care are more likely to be up-to-date with CRCS. The results provide important information that can inform occupation-based public health interventions.